CHARITABLE ACTIVITIES IN MODERN RUSSIA - R. M. Sadykov; N. L. Bolshakova (Вестник университета)
Сharitable organizations and charitable activities in Russia and their role in modern conditions have been considered. Charity in Russia today is a significant and important institution that continues the social policy of the state. The reasons, forms and types of charity have been presented. The innovative forms of charity have been identifed: SMS donations, using charity portals and donation services, purchasing a product or service in favor of charity, charity events, and volunteering. A promising form of charitable activity is volunteering. According to the results of a sociological study, charity is popular among the population: 89.5% of respondents have ever been involved in charity. In general, the respondents have a positive image of charity in Russia. Most of the respondents in one way or another have ever taken part in charity and noted the possibility of participation in the future.